The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1210/jc.2014-2197
|View full text |Cite
|
Sign up to set email alerts
|

Tree-Based Model for Thyroid Cancer Prognostication

Abstract: This study identifies distinct prognostic groups for thyroid cancer and illustrates the importance of patient age to both disease-specific and OS. These findings have implications for patient education and thyroid cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 28 publications
2
35
0
Order By: Relevance
“…Although CART has been used in clinical research, tree-based approaches have been largely underutilized within observational epidemiology. 31,32 Although variations in body composition across racial and ethnic groups are well established, 36 this is the first study to examine racial differences in muscle weakness in diverse sample of older American adults. However, it should be noted that even though the replication of previous work by FNIH was carried out in this analysis, using slow walking speed as the primary outcome variable in the CART models may not have been ideal, particularly for black men and women, given the high prevalence of slow walking speed in the sample.…”
Section: Discussionmentioning
confidence: 99%
“…Although CART has been used in clinical research, tree-based approaches have been largely underutilized within observational epidemiology. 31,32 Although variations in body composition across racial and ethnic groups are well established, 36 this is the first study to examine racial differences in muscle weakness in diverse sample of older American adults. However, it should be noted that even though the replication of previous work by FNIH was carried out in this analysis, using slow walking speed as the primary outcome variable in the CART models may not have been ideal, particularly for black men and women, given the high prevalence of slow walking speed in the sample.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with distant metastatic disease at presentation have a 50% rate of 5-year survival mainly because of the sensitivity of metastatic disease to RAI therapy [1,4]. Age at diagnosis has a strong effect on survival; patients aged ,51 years have a .90% rate of 10-year survival, even with distant disease detected at time of diagnosis [5]. It is estimated that 20% of patients with locoregional disease at presentation will develop distant metastasis at some point in their lifetimes [6].…”
Section: Introductionmentioning
confidence: 99%
“…28,29 Ghaznavi et al reported that the, "Integration of the AJCC stage, ATA risk, and age groups identified six subgroups with differing outcomes: (i) stage I/ATA low-risk, younger and older, 100.0% DSS; (ii) stage I/ATA intermediate-risk, younger and older, 98% DSS; (iii) stage I/ATA high-risk, younger, 95% DSS; (iv) stage I/ATA high-risk, older, 89% DSS; (v) stage II/ATA highrisk, younger, 78% DSS; and (vi) stage II/ATA high-risk, older, 61% DSS." 30,31 Lim et al reported that patients treated with a total thyroidectomy had an increased RFS when compared to those treated with lobectomy with isthmusectomy (hazard ratio: 0.355; 95% CI: 0.127-0.992). Other studies also report the 10-year DSS of the low-risk WDTC to be 95% to 100.0%.…”
Section: Discussionmentioning
confidence: 99%